Distributive Justice and Sustainability Goals in Transboundary Rivers: Case of the Nile Basin - Yalew, S. G.; Kwakkel, J.; Doorn, N. (Frontiers in Environmental Science, 2021)
The importance of cooperation on trans-boundary waters is stated as a target in the United Nations 2030 Agenda for Sustainable Development Goals (SDG6: water). Such cooperation is critical, particularly because trans-boundary water management issues play out across multiple states, SDGs and targets including agriculture, energy, ecosystems, climate adaptation, health, and peace and security. Hence, percentage of trans-boundary basin area within a country that has an ‘operational arrangement’ for water cooperation is used as the main indicator of such cooperation (SDG 6.5.2). Besides the lack of explanations for what exactly constitutes an “equitable and reasonable’ ‘operational arrangement”, it’s understandable that any such arrangements may be shaped by differences in historical, legal, political, and ethical context. Here, we highlight limitations in the existing SDG indicators for monitoring progresses towards sustainable developments in trans-boundary rivers. Using the Nile basin as a case study, we emphasis the role of distributive justice in formulating criteria for ‘equity’ in trans-boundary rivers.